Creation of a cell culture bank: experience of the Pokrovsky Cell Technology Center - E. M. Prikhodko; O. V. Supilnikova; I. V. Maslennikova; N. I. Yenukashvili; A. V. Kotova; V. V. Bagaeva; T. L. Zolina; A. I. Konkina; G. S. atsemirsky (Кардиоваскулярная терапия и профилактика)
Modern research in cell biology places high demands on the model objects used, including cell cultures. These requirements are dictated by the need to avoid artifacts in work and reduce potential risks to the environment associated with biological hazard. The article presents the experience of creating cell culture bank for personal and public storage at the Pokrovsky Cell Technology Center. The main points of managing the collection, incoming quality control, certification, processing, preparation for storage and storage of human biological materials are considered. The developed approaches and work algorithms made it possible to create a collection of early passage cultures consisting of certified samples that meet the requirements for cell cultures for the manufacture of high-tech drugs and biomedical cell products, as well as for research.